Biochemical Markers of Physical Exercise on Mild Cognitive Impairment and Dementia: Systematic Review and Perspectives - Jensen, Camilla Steen; Hasselbalch, Steen Gregers; Waldemar, Gunhild; Simonsen, Anja Hviid (Frontiers in Neurology, 2015)
Background: The cognitive effects of physical exercise in patients with dementia disorders or Mild Cognitive Impairment (MCI) have been examined in various studies; however the biochemical effects of exercise from intervention studies are largely unknown. The objective of this systematic review is to investigate the published results on biomarkers in physical exercise intervention studies in patients with MCI or dementia. Methods: The PubMed database was searched for studies from 1976 to February 2015. We included intervention studies investigating the effect of physical exercise activity on biomarkers in patients with MCI or dementia. Results: A total of eight studies were identified (n= 447 patients) evaluating exercise regimes with variable duration (single session - 3 sessions pr week for 26 weeks) and intensity (light resistance training – high intensity aerobic exercise). Various biomarkers were measured before and after intervention. Seven of the eight studies found a significant effect on their selected biomarkers with a positive effect of exercise on brain-derived neurotrophic factor, cholesterol, testosterone, estradiol, dehydroepiadrosterone and insulin in the intervention groups compared with controls. Conclusion: Although few studies suggest a beneficial effect on selected biomarkers, we need more knowledge of the biochemical effect of physical exercise in dementia or MCI.